An Experimental Study on the Effect of Temperature on the Shear Strength Behavior of a Silty Clay Soil - Henok Hailemariam; Frank Wuttke (Geotechnics, 2022)
In this paper, we report on the results of an experimental study of the yielding and shear strength behavior of a normally consolidated silty clay soil from eastern Germany. The shear strength tests were performed on remolded forms of the soil using a triaxial cell which can regulate the temperature of the specimen. The experimental program comprised a series of pressure stepping compression consolidated drained (CD) triaxial tests at temperatures of 20, 40 and 60 °C. Overall, although the volume change behavior of the soil was found to exhibit some variations with changes in temperature, possibly due to changes in the double layer thickness of the clay fraction of the soil upon heating, the shear strength behavior (in terms of effective angle of internal friction) of the silty clay soil was found to exhibit minor changes with variations in temperature and can be assumed to be independent of temperature for the range considered in this study.